Air pistol shot efficacy under normal and excited conditions/Eficacia en el tiro de la pistola de aire bajo condiciones normales y de excitación - Pablo Cruz Perugachi; Jefferson Rueda Rosales (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
Shooting is practiced mostly by police or military, it has become an Olympic sport where the air pistol test stands out, which requires extreme mental concentration and precision in its movements to achieve effectiveness in the shot. In this work, the authors aim to identify the kinematic data of the arm-weapon complex in normal and excited state during the execution of the shot, considering variables such as heart rate, the effectiveness of the shot and the angles of the main joints (glecohumeral) that allow the execution of the technique. As part of the methodology, this research was implemented in the closed shooting range of the Escuela Superior Militar "Eloy Alfaro" and seven athletes that form the shooting teams of the Ecuadorian Army and Air Force were analyzed. The heart rate (in four phases), the effectiveness of the shot (in three opportunities) and the angle of the glenohumeral joint in resting and excited states were analyzed, where the pertinent comparisons were made. As results of the study, it is shown that the mean values of the heart rate were significantly different (p=0.001), being higher in the excited state. The effectiveness of the shot does not establish significant differences (p=0.620) between states, as well as the glenohumeral joint angles (p=0.209). It is concluded that there are no significant differences in the effectiveness of shooting in excitement and at rest, an indicator of good physical preparation, although there is less effectiveness of shooting in the excited state.